Thermal conductivity assessment of moist building insulation material using a Heat Flow Meter apparatus. (15th April 2023) - EL Assaad, M.; Colinart, T.; Lecompte, T.
Abstract: Thermal conductivity is one of the most important parameters of building insulation materials. This parameter is dependent on the temperature, and on the moisture content for hygroscopic materials. When measured by steady-state methods (with the HFM device and the guarded hot plates), moisture will migrate from the hot side to the cold, influencing the measured heat flux and, thus, the measured thermal conductivity. This study aims to analyze the effects of moisture transfer on the thermal conductivity measurement of wet hygroscopic light building insulation material (namely wood fiber insulation). Several experiments are performed on instrumented samples to evaluate the influence of parameters like the thickness, the mean moisture content, the mean temperature, or the temperature gradient on the measured heat flux, on the temperature and relative humidity distributions and on the time to reach hygrothermal equilibrium. Particularly, the measurement errors made when shortening the experiment are discussed and the moisture dependence of true thermal conductivity is evaluated experimentally by considering the notions of apparent and diffusive thermal conductivities. Last, by using a validated heat and moisture transfer model, this dependency is compared to the one predicted by the methods proposed in the standards EN 12664 or ISO 10051. Highlights: Thermal conductivity of moist insulation is measured with HFM apparatus. Influence of mean moisture content and temperature, and thickness is investigated. Moisture dependence of true thermal conductivity is evaluated. Shorten the experiment overestimates thermal conductivity of moist sample. Methods proposed in the standards EN 12664, or ISO 10051 are limited.